A fully coupled method for numerical modeling and dynamic analysis of floating vertical axis wind turbines. (July 2017) - Cheng, Zhengshun; Madsen, Helge Aagaard; Gao, Zhen; Moan, Torgeir
Abstract: Offshore wind energy is one of the most promising renewable energy resources and an increasing interest arises to develop floating vertical axis wind turbines (VAWTs), which have the potential to reduce the cost of energy. Assessment of the performance of floating VAWTs requires sophisticated fully coupled aero-hydro-servo-elastic simulation tools, which are currently limited. This paper aims to develop a fully integrated simulation tool for floating VAWTs. Based on the actuator cylinder (AC) flow model, aerodynamic modeling of floating VAWTs is established with consideration of the effects of turbulence, dynamic inflow and dynamic stall. The developed aerodynamic code is then coupled with the code SIMO-RIFLEX to achieve a fully coupled tool, i.e. SIMO-RIFLEX-AC, which can account for the aerodynamic, hydrodynamics, structural dynamics and controller dynamics with high fidelity. A series of code-to-code comparisons with the codes HAWC2 and SIMO-RIFLEX-DMS are carried out using a landbased VAWT and a semi-submersible VAWT, and reveal that the present code can predict the aerodynamic loads and dynamic responses accurately. Moreover, the code SIMO-RIFLEX-AC can predict more accurate responses than the code SIMO-RIFLEX-DMS, such as the platform motions, tower base bending moments and tension in mooring lines. Highlights: Aerodynamic modeling of floating VAWTs is established using the Actuator Cylinder (AC) flow method. A fully coupled aero-hydro-servo-elastic simulation tool, i.e. SIMO-RIFLEX-AC, is developed for floating VAWTs. The developedsimulation tool is verified to be accurate by a series of code-to-code comparisons. This simulation tool can be used for design and response analysis of different floating VAWT concepts.